Narration in the Transitional Cinema: The Historiographical Claims of the Unauthored Text / La narration dans le cinéma de transition : les prétentions historiographiques du texte sans auteur - Keil, Charlie (Cinémas, 2011)
Though our knowledge of the transitional era has increased substantially over the last few decades, incorporating studies of pivotal institutions, exhibition and reception contexts, and forces of regulation and circulation, formal analysis of the period’s films is still indebted to the singular example of D.W. Griffith, identified as the instigator of the “narrator system” in Tom Gunning’s influential book, D.W. Griffith and the Origins of the American Narrative Film. But the historical accident that resulted in Griffith’s films surviving when those of his contemporaries largely disappeared has defined most historians’ approach to charting a history of narrational changes during the pivotal years of 1908-1913. Rather than challenge Griffith’s importance as an enterprising and influential filmmaker, historians require the means to better contextualize Griffith’s contributions, rewriting in the process a formal history that can incorporate authorship without being defined by it as a governing principle. To this end, this essay will use the opportunity provided by the ongoing restoration and distribution of Thanhouser films from 1910-1913 to investigate how the “unauthored text” from this period can aid in our endeavours to expand the contours of the historiography of the transitional era.